Arrhythmias in Patients after Surgical Myocardial Revascularization - N. U. Zakirov; A. G. Kevorkov; A. S. Rasulov; E. Y. Tursunov (Рациональная фармакотерапия в кардиологии)
This work represents literature review data regarding the study of the effect of surgical myocardial revascularization on the processes of electrical myocardial instability underlying the onset of life-threatening ventricular arrhythmias, as well as the possibilities for its non-invasive assessment by studying the heart rhythm variability and turbulence. Analyzed data demonstrated that, relying only on the presence of a viable myocardium, it is often impossible to predict the positive effect of revascularization on the prognosis in patients, especially those with reduced myocardial contractility. Considering the well-studied relationship between myocardial remodeling and neurohormonal activation, such non-invasive methods for assessing vegetative regulation of cardiac activity, as heart rate variability and turbulence may provide additional diagnostic information. The literature data indicate that heart failure, ventricular arrhythmias and recurrences of angina and myocardial infarction are the main problems that determine an unfavorable outcome in the postoperative period. There is important evidence that violations of the vegetative regulation of the heart, the heterogeneity of repolarization processes in the myocardium are integral indicators of the morphofunctional changes occurring in the process of coronary heart disease (CHD) progression. The role of indicators of heart rate variability and turbulence as predictors of sudden cardiac death was proved, mainly due to fatal ventricular heart rhythm disorders and cardiovascular mortality. Along with this, changes in these indicators, and their prognostic role in patients with CHD in revascularization are the subject of discussion, which determines the relevance of further studies on the effect of various methods of revascularization on the electrical instability of the myocardium, as one of the most important factors in the development of life-threatening ventricular arrhythmias that are predictors of sudden cardiac death, especially in patients who previously had acute myocardial infarction. Besides it is important to study the effect of myocardial revascularization on the indicators of cardiac autonomic regulation and the possibility of their use as prognostic criteria before and after surgery.